159k views
1 vote
What this simplified

What this simplified-example-1

1 Answer

5 votes

Answer:


\frac{3b\sqrt[3]{c^(2)} }{a^(2) }

Explanation:

∛(27a⁻⁶b³c²)

To simplify, first apply the cube root the each of the terms. Keep in mind this rule:
\sqrt[n]{a^(m)}  = (\sqrt[n]{a})^(m) = a^(m/n)

∛27 = 3 (because 3*3*3 = 27)

∛a⁻⁶ =
a^(-6/3) =
a^(-2) =
(1)/(a^(2))

∛b³ =
b^(3/3) =
b^(1) = b

∛c² =
c^(2/3)

∛(27a⁻⁶b³c²)

=
\frac{3b\sqrt[3]{c^(2)} }{a^(2) }

Simplified form generally follows these rules:

No negative exponents

No fraction exponents

Keep in fractional form

Reduce numerical values

User Dani Amsalem
by
5.3k points